Hydrogenation of Epoxidized Natural Rubber - กลิ่นไกล วารุณี; คาวาฮา เซอิชิ (Frontiers in Engineering Innovation Research, 2006)
Hydrogenation of natural rubber (NR) is an important technique to improve properties of the rubber. i.e. good aging resistance and high temperature usage. This has been carried out in diene elastomer by conversion of an unsaturated polymer to a saturated polymer using homogeneous and heterogeneous catalyst. However. hydrogenation of functionalized rubbers such as epoxidized NR, is quite difficult due to the functional groups interfere during the reaction. Thus. it is necessary to investigate the condition to prepare the hydrogenated rubber from ENR. In the present work. natural rubber which was deproteinized with proteolytic enzyme. was epoxidized in latex state with formic acid and hydrogen peroxide was hydrogenated in high-pressure autoclave with hydrogen gas in the presence of catalyst. The relationship between structure and properties of resulting hydrogenated NR (HNR) and epoxidized NR (HEDNR) are investigated. The hydrogenated rubber product was characterized by FTIR spectroscopy . H-MR spectroscopy, DSC and TGA. The extent of hydrogenation was dependent upon reaction time, temperature and catalyst. There is no change in amount of epoxy group content of the EDPNR after the hydrogenation. Natural rubber was also investigated for a comparative study.